GEOSTRATEGIC ASPECT OF PASSENGER HIGH-SPEED RAILWAY COMMUNICATION - Савчук, І. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Geostrategic aspect of passenger high-speed railway communication is an important element of the national defense strategy. The use of this mode of transport creates new opportunities for moving troops and at the same time gives rise to certain problems with the placement of the respective units of the armed forces of the country. The questions of defense organization of infrastructure elements of high-speed railway communication and their deployment in residential places, especially in the cities are of great importance. Keywords: geostrategy, high-speed railway communication, passenger transportation.